Bile acid elevation after Roux-en-Y gastric bypass is associated with cardio-protective effect in Zucker Diabetic Fatty rats. (December 2015) - Kumar, Sunil; Lau, Raymond; Hall, Christopher; Palaia, Thomas; Brathwaite, Collin E.; Ragolia, Louis
Abstract: Background: Roux-en-Y gastric bypass (RYGB) may improve cardiometabolic risk through alteration of bile acids and L-PGDS levels. Objective: The objective of this study was to investigate the effect of RYGB on aortic wall thickness, in relation to bile acid and L-PGDS metabolism. Methods: Zucker diabetic fatty (ZDF) rats were divided into two groups, ad lib (n = 4), and RYGB (n = 6). Bile acid and L-PGDS were measured presurgery and fourteen weeks post-surgery. Results: Elevation of bile acid levels following RYGB in Zucker Diabetic Fatty (ZDF) rodents was observed, as compared to ad lib . RYGB in ZDF rodents led to a significantly decreased aortic wall thickness (25%) as compared to ad lib control. Although bile acid metabolism is implicated in these alterations, other mediators are likely involved. Our laboratory has demonstrated lipocalin prostaglandin D2 synthase (L-PGDS) is a kno n cardiometabolic modulator that also functions as a bile acid binding protein. Therefore, L-PGDS levels were measured and a significant elevation was observed with RYGB compared to ad lib control. Conclusion: Based on these findings, RYGB showed beneficial effect on aortic wall thickness, possibly through bile acids and L-PGDS elevation in a severely obese and diabetic rodent model. Highlights: RYGB ameliorated cardiometabolic risk through alteration of bile acid levels. Bile acid levels significantly increased 14 week post RYGB. L-PGDS levels were found significantly elevated after 14 week. RYGB in ZDF rodents led to a significant decrease in aortic wall thickness.